Medical and health library a cooperat ive project to provide medical and health information to all. - Human Info NGO (Humanity Information Projects); Payon Center for International Development and Technology transfer o f the Tulane University (Antwerp, Belgium: Human Info NGO, 1999)
This CD-ROM library 1.1 contains 300 publications in the field of me dicine and health including 100 HIV/AIDS related publications.
Edited and coordinated by the Human Info NGO (Humanity Information P rojects) and the Payon Center for International Development and Technol ogy transfer of the Tulane University, in cooperation with numerous org anisations and agencies.
Systems requirements: Windows 3.x, Windows 95/98 & NT
English
Keywords: Medicine -- Information services; Health -- Information services